ASEAN’s Role in the Formulation of the South China Sea Code of Conduct (CoC) and Its Implications for Regional stability - Paul, John (PT. Batari Edu Calya, 2025)
The South China Sea represents one of the most contested maritime spaces globally, characterised by its economic, strategic, and geopolitical significance. The region’s vast natural resources and function as a vital international trade route have made it a focal point of disputes involving several ASEAN member states and the People’s Republic of China (PRC). To mitigate tensions and promote peace, ASEAN has sought to develop a binding Code of Conduct (CoC), building on the 2002 Declaration on the Conduct of Parties in the South China Sea (DoC). This study employs a qualitative juridical-normative approach, utilizing literature review and descriptive-analytical methods to examine ASEAN’s role in the formulation of the CoC and its broader implications for regional security governance. Findings reveal that ASEAN plays a multifaceted role as a diplomatic mediator, normative forum, and integrative platform; however, divergent national interests hinder its effectiveness, China’s negotiation dominance, and external pressures from global powers, such as the United States. While the CoC offers significant potential to enhance trust, prevent conflict escalation, and reinforce the legal framework established by UNCLOS 1982, its effectiveness depends on ASEAN’s internal cohesion and the willingness of external actors to commit to binding agreements. This article concludes that a robust and legally binding CoC is crucial for strengthening ASEAN’s centrality and maintaining stability in the South China Sea.